Reporting of attitudes- a systematic review and quantitative analysis of research publications in palliative care journals - Kumar, Senthil Paramasivam; Sisodia, Vaishali (Asian Journal of Medical Research, 2017)
Objective: This study aimed to perform a quantitative analysis of research publications in palliative care journals for reporting of articles on attitudes. Settings and Design: Systematic review of palliative care journals Methods: Twelve palliative care journals were searched for articles with ’attitudes’ in title of the articles published from 2006-2011. The reporting rates of all journals were compared. The selected articles were categorized into assessment and treatment which were subsequently grouped into original and review articles. The original articles were sub-grouped into qualitative and quantitative studies, and the review articles were grouped into narrative and systematic reviews. Each subgroup of original articles category was further classified according to study designs and target sample populations. Results: The overall reporting rate among all journals was 2.06% (59/2854) and Indian Journal of Palliative Care (IJPC) had the highest reporting rate of 3.70% (4/108) followed by BMC Palliative Care (BMCPC) at 3.37% (3/89), and Palliative Medicine (PM) at 2.91% (14/481). Conclusions: The overall reporting rate for ’attitudes’ articles in palliative care journals were 2.06% and there were no randomized clinical trials and systematic reviews found. The study findings indicate a lack of adequate evidence base for attitudes in palliative care literature.